Beginning Windows Phone 7 Development - Lee, Henry; Chuvyrov, Eugene; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Microsoft is injecting new energy into the smart phone marketplace with the sophisticated Windows Phone 7. This new energy equates to new opportunities for you, the mobile developer. Beginning Windows Phone 7 Development has been written specifically to help you seize these opportunities and begin creating applications for this exciting new mobile device platform. Beginning Windows Phone 7 Development starts with the basics, walking you through the process of downloading and setting up the right development tools, including Visual Studio, Expression Blend, Silverlight SDK, and Windows Phone SDK. The book then takes you step-by-step though the development process as you build and deploy a complete application with a highly sophisticated user interface. Finally, you'll receive step-by-step instructions on selling your applications through the Microsoft Phone Marketplace.
The Essentials of Windows Phone 7 Application Development -- Introducing Windows Phone 7 and the Windows Phone Platform -- Building Windows Phone 7 Applications -- Using Cloud Services As Data Stores -- Catching and Debugging Errors -- Packaging, Publishing, and Managing Applications -- Using Windows Phone7 Technologies -- Working with the Accelerometer -- Application Bar -- WebBrowser Control -- Working with Controls and Themes -- Integrating Applications with the Windows Phone OS -- Creating Trial Applications -- Internationalization -- Isolated Storage -- Using Location Services -- Media -- Working with the Camera and Photos -- Push Notifications -- Reactive Extensions for.NET -- Security.
Keywords: Computer science; Computer Science; Computer Science, general